Microbial assemblages in soil microbial succession after glacial retreat in Svalbard (high arctic) - Kastovská, Klára; Elster, Josef; Stibal, Marek; Santrůcková, Hana (Microbial ecology, 2005)
Microbial community composition (cyanobacteria and eukaryotic microalgae abundance and diversity, bacterial abundance, and soil respiration) was studied in subglacial and periglacial habitats on five glaciers near Ny-Alesund, Svalbard (79 degrees N). Soil microbial communities from nonvegetated sites (subglacial, recently deglaciated, and cryoconite sediments) and sites with plant cover (deglaciated some hundreds of years ago) were analyzed. Physicochemical analyses (pH, texture, water content, organic matter, total C and N content) were also performed on the samples. In total, 57 taxa of 23 genera of cyanobacteriaand algae were identified. Algae from the class Chlorophyceae (25 species) and cyanobacteria (23 species) were richest in biodiversity. The numbers of identified species in single habitat types were 23 in subglacial, 39 inbarren, 22 in cryoconite, and 24 in vegetated soils. The highest cyanobacterial and algal biovolume and cell numbers, respectively, were present in cryoconite (13x10(4) microm3 mg-1 soil and 508 cells per mg of soil), followed by barren (5.7x10(4) and 188), vegetated (2.6x10(4) and 120), and subglacial (0.1x10(4) and 5) soils. Cyanobacteria prevailed in all soil samples. Algae (mainly green algae) were present only as accessory organisms. The density of bacteria showed a slightly different trend to that of the cyanobacterial and algal assemblages. The highest number of bacteria was present in vegetated (mean: 13,722x10(8) cells per mg of soil dry wt.), followed by cryoconite (3802x10(8)), barren (654x10(8)), and subglacial (78x10(8)) soils. Response of cyanobacteria and algae to physical parameters showed that soil texture and water content are important for biomass development. In addition, it is shown that nitrogen and water content are the main factors affecting bacterial abundance and overall soil respiration. Redundancy analysis (RDA) with forward selection was used to create a model explaining variability in cyanobacterial, algal, and bacterial abundance. Cryoconites accounted for most of the variation in cyanobacteria and algae biovolume, followed by barren soils. Oscillatoriales, desmids, and green coccoid algae preferred cryoconites, whereas Nostocales and Chroococcales occurred mostly in barren soils. From the data obtained, it is evident that of the studied habitats cryoconite sediments are the most suitable ones for the development of microbial assemblages. Although subglacial sediments do not provide as good conditions as cryoconites, they support the survival of microbial communities. Both mentioned habitats are potential sources for the microbial recolonization of freshly deglaciated soil after the glacier retreat.
Keywords: Arktida; půdní mikrobiologie; Arctic Regions; sinice; Ecosystem; půda; Soil; Cyanobacteria; Ice; Chlorophyta; Soil Microbiology; Eukaryota; Colony Count, Microbial; počet mikrobiálních kolonií; ekosystém; led